(untitled) (Homiletic, 2025)
This article claims that preachers use words well (that is, ethically) when they use them beautifully, so that the sermon becomes compelling. This is done by preaching words that are fresh, in forms that suit the subject matter and delight listeners, in an effort to arouse and shape the affections of the congregation. Drawing on the work of poet-preacher George Herbert as an exemplar of beautiful Christian speech, this paper discusses the role of beauty in homiletical ethics and turns to Herbert for inspiration.